2018
DOI: 10.1261/rna.066753.118
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric padlock and iLock probes for increased efficiency of targeted RNA detection

Abstract: Many approaches exist to detect RNA using complementary oligonucleotides. DNA ligation-based techniques can improve discrimination of subtle sequence variations, but they have been difficult to implement for direct RNA analysis due to the infidelity and inefficiency of most DNA ligases on RNA. In this report, we have systematically studied if ribonucleotide substitutions in padlock probes can provide higher catalytic efficiencies for Chlorella virus DNA ligase (PBCV-1 DNA ligase) and T4 RNA ligase 2 (T4Rnl2) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In summary, we confirmed the previously reported tolerance of SplintR ligase for single-nucleotide mismatches at the ligation site [ 26 , 30 , 37 ]. Our experimental data show that the specificity of SCRINSHOT largely depends on the stringent hybridization of the 20-nucleotide-long padlock arms (40 nucleotides in total) and less on the specificity of the used ligase.…”
Section: Resultssupporting
confidence: 91%
“…In summary, we confirmed the previously reported tolerance of SplintR ligase for single-nucleotide mismatches at the ligation site [ 26 , 30 , 37 ]. Our experimental data show that the specificity of SCRINSHOT largely depends on the stringent hybridization of the 20-nucleotide-long padlock arms (40 nucleotides in total) and less on the specificity of the used ligase.…”
Section: Resultssupporting
confidence: 91%
“…Since the DNA oligonucleotides will be directly used for qPCR, the introduction of “tails” (sequences) that are not found naturally in the genome enables the design of primers that are highly specific to the DNA template. Similar in concept to Padlock probes, the key differentiator is that squaramide chemical ligation enables efficient ligation irrespective of nucleic acid substrate, allowing RNA detection that is otherwise challenging with ligase enzymes …”
Section: Resultsmentioning
confidence: 99%
“…[33] Since the DNAo ligonucleotides will be directly used for qPCR, the introduction of "tails" (sequences) that are not found naturally in the genome enables the design of primers that are highly specific to the DNAtemplate.Similar in concept to Padlock probes, [34,35] the key differentiator is that squaramide chemical ligation enables efficient ligation irrespective of nucleic acid substrate,a llowing RNAd etection that is otherwise challenging with ligase enzymes. [36] In designing our pair of RNA-detecting DNAo ligonucleotides ( Figure 5A), we split each oligonucleotide into a20mer region that hybridises to the RNAtarget and a10-mer 5'tail for PCR primer binding.T he two 20-mer regions were designed to minimise self-complementarity,w hich would otherwise lead to template-independent ligation, and to be highly specific to the target as determined by BLAST [37] alignment against ar eference database.T he 10-mer sequences were designed to be non-complementary to the target, and provide ar elatively unstructured tail on which PCR primers can efficiently bind to for amplification, the latter being determined by mfold. [38] As ap roof of concept, we initially designed DNA oligonucleotides that target a1 00-mer RNA( Figure 5A and Supporting Information, Table S9).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Currently, alternative protocols that involve the direct probing of RNA with PLPs and RCA, such as SCRINSHOT (16) and targeted ExSeq (17) have also exhibited improved transcript detection efficiency. However, PBCV-1 DNA ligase used in these protocols have shown high tolerance for mismatches in ligation and extensive optimization would have to be undertaken for different tissue types to prevent off-target detection (13,16) . The increased efficiency of dRNA has allowed for improved detection of lower expressed transcripts, which would otherwise be challenging to detect with the cDNA approach.…”
Section: Discussionmentioning
confidence: 99%
“…Direct hybridization and probing of mRNA in situ for improved efficiency has been attempted with different commercially available ligases, including Chlorella virus DNA ligase (PBCV-1 DNA ligase), but showed high tolerances of mismatches for ligation (12) , and consequently worse specificity compared to cDNA template DNA ligation using thermophilic DNA ligases. Recently, it was reported that T4-RNA Ligase 2 showed good ligation efficiency with 3'-RNA/5'-DNA PLPs (Chimeric PLPs) on RNA templates, and exhibits higher ligation fidelity on single nucleotide variations, compared to PBCV-DNA ligase (13) . Here we evaluate such a direct RNA (dRNA) chemistry in situ with HybISS (HybRISS: Hybridization-based RNA in situ sequencing) that targets RNA with chimeric PLPs while still retaining the fundamental benefits of ISS technology.…”
Section: Introductionmentioning
confidence: 99%